Comparative Analysis of Elderly Patients Undergoing Radical Cystectomy With Ureterocutaneostomy or Ileal Conduit With a Special Focus on Bowl Complications Requiring Surgical Revision - Mally, David; John, Patricia; Pfister, David; Heidenreich, Axel; Albers, Peter; Niegisch, Günter (Frontiers in Surgery, 2022)
Objectives: Ileal conduits (IC) carry an additional perioperative complication risk due to the bowel procedure. This analysis compares surgical outcomes in patients ≥75 years of age with ureterocutaneostomy (UCN) and IC after cystectomy (Cx). Methods: Data of 527 patients included in a retrospective cystectomy database of two high volume centers (2008-2020) were queried to identify elderly patients (≥75 years) who underwent Cx either with ileal conduit (IC) or ureterocutaneostomy (UC). Patient characteristics of all patients (age, BMI, Charlson Comorbidity Index (CCI)), perioperative parameters (operation time, blood loss, transfusions, tumor stage), and postoperative complications (clavien >IIIA, intensive care unit (ICU) stay) were compared. As special focus, bowel complications requiring revision (rBC) were analysed. In IC patients, the rate of ureteral implantation stenosis (USt) was recorded. As a population of special interest, patients ≥80 years were analyzed separately. Categorical data were compared using Fisher exact test, and continuous data were compared using Mann-Whitney U test. Results: A total of 163 patients ≥75 years (125 IC, 38 UCN) were identified. UCN patients were older and presented with a higher CCI, though differences were not statistical different. Palliative intended was more frequently in UCN patients (37% vs. 10%). Operation time in UCN was significantly shorter (233 vs 305 min, p=0.02), while blood loss and transfusion rate were comparable. Overall complication rate (Clavien-Dindo grade IIIA – IVB) was comparable (UCN 34% vs IC 37%). Though, rBC was a rare complication in UCN (3/38) as compared to IC patients (15/125). Frequency of postoperative ICU stay, (UCN 16% vs IC 16%) and 90-d mortality did not differ (UCN 3/38 patients, IC 5/125 patients). Regarding long-term follow up, USt requiring revision or permanent stenting were seen in 18/125 (14%) IC patients. In patients >80 years results were comparable to the main cohort. Low event rate regarding complications and bias inherent of a retrospective analysis (selection bias, unequal distribution in case numbers) precludes detection of statistical differences regarding patients’ characteristics and overall complication rate. Conclusion UCN is an alternative to IC in elderly and/or frail patients. Severe bowel complications are numerically less frequent and operation time is minimized.